ASD library backpack - Azmi, Nor Azlina; Supran, Nur Fatin Atiqah; Shahimi, Nurul Najwa (Universiti Teknologi MARA, Kedah, 2019)
One of public library’s main objectives is to advocate for equitable access to information and knowledge for communities world-wide that supports the democratic process, shared understanding and community well-being (IFLA 2018). However, the community of special needs individuals are often overlooked and underserved. (Nur Izzaidah and Nazean Jomhari, 2012). Moreover, Parents of Autistic children are afraid of exposing their autism children to public places such as library as Children with autism experience difficulties in social interaction and communication which are often manifested by extremely challenging behaviour that is difficult to manage.(Tansley, 2013). Being judged, stared at or told to be quiet are among the reasons that children with autism do not visit their local library. A library should be seen as a safe space for all and they are by their very nature naturally inclusive. A busy library can be a challenging place for someone with autism. The idea for a Sensory Backpack collection was born after we found out that none of the the public library have focused on this creation. We decided to use this backpack to help students with autism feel welcome at library. In this backpack it consists of sensory books, sensory games (Dwibahasa) and calm toys with different themes for the purpose of children to learn Calm Down, develop Focus, and Social Skills and to minimize anxiety. It is hope that by having this sensory backpack, the library can best serve children with autism.